2017
DOI: 10.3390/ijms18112261
|View full text |Cite
|
Sign up to set email alerts
|

P2X4 Receptor-Dependent Ca2+ Influx in Model Human Monocytes and Macrophages

Abstract: Monocytes and macrophages express a repertoire of cell surface P2 receptors for adenosine 5′-triphosphate (ATP) a damage-associated molecular pattern molecule (DAMP), which are capable of raising cytoplasmic calcium when activated. This is achieved either through direct permeation (ionotropic P2X receptors) or by mobilizing intracellular calcium stores (metabotropic P2Y receptors). Here, a side-by-side comparison to investigate the contribution of P2X4 receptor activation in ATP-evoked calcium responses in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Consistent with these data, 5‐BDBD has been reported as a moderately potent inhibitor of human and rodent recombinant P2X4 receptors, with limited effectiveness at submicromolar concentrations (Abdelrahman et al, 2017; Ase et al, 2015; Balazs et al, 2013; Coddou, Sandoval, Hevia, & Stojilkovic, 2019). The data presented here are also in agreement with recent studies demonstrating inhibition of endogenous P2X4 receptor activity in human monocyte‐derived macrophages (Layhadi & Fountain, 2017) and human CD4 + T cells (Ledderose et al, 2018). Furthermore, the current study reported 5‐BDBD to be ineffective at inhibiting Ca 2+ responses induced by saturating concentrations of ATP.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these data, 5‐BDBD has been reported as a moderately potent inhibitor of human and rodent recombinant P2X4 receptors, with limited effectiveness at submicromolar concentrations (Abdelrahman et al, 2017; Ase et al, 2015; Balazs et al, 2013; Coddou, Sandoval, Hevia, & Stojilkovic, 2019). The data presented here are also in agreement with recent studies demonstrating inhibition of endogenous P2X4 receptor activity in human monocyte‐derived macrophages (Layhadi & Fountain, 2017) and human CD4 + T cells (Ledderose et al, 2018). Furthermore, the current study reported 5‐BDBD to be ineffective at inhibiting Ca 2+ responses induced by saturating concentrations of ATP.…”
Section: Discussionsupporting
confidence: 92%
“…The agonist profile of ATP on DH82 cells demonstrated pharmacological similarities to the recombinant canine P2X4 receptor [41], as well as studies of endogenous P2X4 receptors in a human macrophage cell model [34]. BzATP induced partial Ca 2+ responses in DH82 cells with significantly lower potency compared to ATP, consistent with the recent report that BzATP is a partial agonist of recombinant canine P2X4 receptors [41].…”
Section: Discussionsupporting
confidence: 82%
“…To date, the DH82 canine macrophage cell line has primarily been utilized as a model of viral and protozoan infection [23][24][25], such as for the study of canine distemper and its oncolytic potential [55][56][57]. Although studies have described the expression of functional P2 receptors in human or rodent macrophages and macrophage cell lines [8,10,11,34], studies directly investigating P2 receptors in canine macrophages have been absent. The current study described, for the first time, the expression and function of P2 receptors in DH82 cells, demonstrating a primary role for cell surface P2Y 2 receptors in nucleotide-mediated Ca 2+ mobilization through PLC/IP 3 signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…1A). This finding is in accordance with previous studies reporting functional evidence for these receptors in monocyte-derived human macrophages (44)(45)(46)(47)(48).…”
Section: Human Macrophages Express Multiple P2x Receptorssupporting
confidence: 93%